Respostas
respondido por:
1
PA (x + 3; 4x + 2; x - 1)
(4x + 2) - (x + 3) = r
(x - 1) - (4x + 2) = r
r = r
(4x + 2) - (x + 3) = (x - 1) - (4x + 2)
4x + 2 - x - 3 = x -1 - 4x - 2
4x - x - x + 4x = -1 - 2 + 3 - 2
6x = -2
x = -2/6
x = -1/3
PA(-1/3 + 3 ; 4.-1/3 + 2 ; -1/3 - 1)
PA( (-1 +9)/3 ; (-4/3 + 2) ; ((-1 - 3)/3)
PA(8/3 ; ((-4 + 6)/3) ; -4/3)
PA(8/3 ; 2/3 ; -4/3)
Espero ter ajudado.
(4x + 2) - (x + 3) = r
(x - 1) - (4x + 2) = r
r = r
(4x + 2) - (x + 3) = (x - 1) - (4x + 2)
4x + 2 - x - 3 = x -1 - 4x - 2
4x - x - x + 4x = -1 - 2 + 3 - 2
6x = -2
x = -2/6
x = -1/3
PA(-1/3 + 3 ; 4.-1/3 + 2 ; -1/3 - 1)
PA( (-1 +9)/3 ; (-4/3 + 2) ; ((-1 - 3)/3)
PA(8/3 ; ((-4 + 6)/3) ; -4/3)
PA(8/3 ; 2/3 ; -4/3)
Espero ter ajudado.
nanau:
Obrigada mais uma vez.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás